stimm : generating knowledge through lived experiences - Vigdís Birna Grétarsdóttir 2002- (2024)
This research paper is written alongside the making of my individual graduation work towards a BA-degree in dance from the Iceland University of the Arts. Titled stimm, the performance explores the act of stimming as movement research. How playing with staging that corporeal reality in different ways can generate knowledge. In the process of making this performance I worked with an all-autistic team of non-men. Through the making of the performance, we aimed to give space to knowledge outside of the status quo. Knowledge that is lived and experienced by the very people that the knowledge is about, in this case, autistic people. In this essay I will elaborate on my need for working with an all-autistic team in this process. How together we can dream of a world that works for us, not against us. How letting people into that world has the potential to generate knowledge beyond our ideas of knowledge. This essay is born out of a need for role models and resources around autism in the performing arts. It is an attempt to be that role model myself and to both create new resources and give space to the ones we already carry in our bodies.